2017
DOI: 10.5194/acp-2017-967
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dome effect of black carbon and its key influencing factors: A one-dimensional modelling study

Abstract: Black carbon (BC) has been identified to play a critical role in aerosol-planet boundary layer (PBL) interaction and further deterioration of near-surface air pollution in megacities, which has been named as its "dome effect". However, the impacts of key factors that influence this effect, such as the vertical distribution and aging processes of BC, and also the underlying land surface, have not been quantitatively explored yet. Here, based on available in-situ measurements of meteorology and 15 atmospheric ae… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 61 publications
5
46
1
1
Order By: Relevance
“…In addition to this, aerosols and their association with the stability of the lower atmosphere increases the regional uncertainties (Qiu et al, ). Recent studies reveal that the heating efficiency of absorbing aerosol is more in the upper boundary layer compared to lower boundary layer height (Ding et al, ; Wang et al, ). It has been shown by earlier researchers that absorbing aerosols below clouds may increase cloud cover by destabilizing the planetary boundary layer and, on the other hand, it is also probable that it reduces cloud cover by reducing surface fluxes (Feingold et al, ; Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, aerosols and their association with the stability of the lower atmosphere increases the regional uncertainties (Qiu et al, ). Recent studies reveal that the heating efficiency of absorbing aerosol is more in the upper boundary layer compared to lower boundary layer height (Ding et al, ; Wang et al, ). It has been shown by earlier researchers that absorbing aerosols below clouds may increase cloud cover by destabilizing the planetary boundary layer and, on the other hand, it is also probable that it reduces cloud cover by reducing surface fluxes (Feingold et al, ; Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The BC issue has been noticed in recent years in China, including its temporal variations, emission sources and climate effect (Cao et al, 2006(Cao et al, , 2009Yang et al, 2009;Wang et al, 2017a;Huang et al, 2014) as well as its "dome effect" in modifying the boundary layer and enhancing haze pollution in megacities (Ding et al, 2016b;Wang et al, 2018). Organic matter (OM) is a large contributor to PM 2.5 in China (15-51 % of PM 2.5 ; Wang et al, 2017c), especially in the Yangtze River Delta (YRD) region, which is one of the most densely populated city clusters in eastern China and also an important agricultural center, with crops planted in both cold and warm seasons (Ding et al, 2013a). In the YRD region, the OM fraction is 20-40 % of PM 2.5 (Wang et al, 2017c, b) due to the influence of complicated combustion sources; therefore, it is a highly possible that BrC is a contributor to aerosol light absorption in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Organic matter (OM) is a large contributor to PM 2.5 in China (15-51 % of PM 2.5 ; Wang et al, 2017c), especially in the Yangtze River Delta (YRD) region, which is one of the most densely populated city clusters in eastern China and also an important agricultural center, with crops planted in both cold and warm seasons (Ding et al, 2013a). In the YRD region, the OM fraction is 20-40 % of PM 2.5 (Wang et al, 2017c, b) due to the influence of complicated combustion sources; therefore, it is a highly possible that BrC is a contributor to aerosol light absorption in this region. However, studies concerning BrC in China, especially in the YRD region, have still been limited up to now.…”
Section: Introductionmentioning
confidence: 99%
“…Quan et al () found that the development of the boundary layer during the aerosol pollution episode was suppressed due to the decrease of surface level solar radiation and sensible heat flux. Wang et al () observed a decline of 3.6 W/m 2 in sensible heat flux due to the dimming effect of aerosols. A decrease in sensible heat flux by 10–30 W/m 2 was reported by Miao et al () over Beijing, China, which is in the range of values observed over IGP and WI.…”
Section: Resultsmentioning
confidence: 99%
“…Aerosols hinder the boundary layer evolution by changing the surface buoyancy flux and latent and sensible heat fluxes (Yu et al, ). If absorbing aerosol layer is at the top or above the boundary layer, the warm air strengthens the capping inversion and hence lowers the boundary layer height (Ding et al, ; Wang et al, ; Yu et al, ). In order to investigate further the effect of aerosols on the atmospheric stability, the diurnal variation of the vertical profiles of temperature anomaly (with feedback‐without feedback) due to aerosol forcing is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%